KONTRIBUSI ANTARA KEKUATAN OTOT LENGAN DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN SERVIS BAWAH DALAM PERMAINAN BOLA VOLI PADA SISWA SMK NEGERI 1 KOTABARU - Hasruddin - (STKIP Paris Barantai, 2015)
This study is the kind of research the descriptive. This study aims to know: (1) To know whether there is the contribution between the power of muscle arm with the ability to for down on the game volleyball students SMK Negeri 1 Kotabaru. (2) To know whether there is the contribution between coordination eye-hand with the ability to for down on the game volleyball students SMK Negeri 1 Kotabaru. (3) To know whether there is the contribution between the power of muscle arm and coordination eye-hand with the ability to for down on the game volleyball students SMK Negeri 1 Kotabaru.The population is students SMK Negeri Kotabaru. Samples used is the male students SMK Negeri 1 Kotabaru as much forty people. The techniques determination of these samples are with the ramdomly with the way the lottery (Simple Random Sampling).Â Analysis technique used data is analysis the descriptive and analysis infernsial through the SPSS 20 on degree significantÎ±0,05. The results of research suggests that: (1) There is the contribution between the power of muscle arm with the ability to for down on the game volleyball students SMK Negeri 1 Kotabaru, by 27,7%. (2) There is the contribution between coordination eye-hand with the ability to for down on the game volleyball students SMK Negeri 1 Kotabaru, by 20,9%. (3) There are contributions significant in together between the power of muscle arm and coordination eye-hand with the ability to for down on the game volleyball students SMK Negeri 1 Kotabaru, with the value of F:11,042 and sig (p)=0,000.Â Key words: The power of muscle arm, coordination eye-hand, volleyball.